Chronic Cystoisospora belli infection in an immunocompetent Myanmar refugee – microscopy is not sensitive enough. Issue 1 (December 2016) - Woon, Sze-Ann; Yang, Rongchang; Ryan, Una; Boan, Peter; Prentice, David
Abstract Background Cystoisosporiasis is an opportunistic infection seen more commonly in patients with acquired immunodeficiency syndrome. Although uncommon, Cystoisospora infection can occur in immunocompetent individuals but tend to be benign and self-limiting. Chronic infection however, has been described but diagnosis can often be challenging and requires a high clinical index of suspicion. Case presentation We present a case of delayed diagnosis ofCystoisospora belli (C. belli ) in an immunocompetent 28-year-old refugee from Myanmar. She had a history of chronic diarrhea where exhaustive investigations over many years failed to reveal a diagnosis.Cystoisospora belli cysts were finally detected in stool 4 years after investigation commenced, and PCR testing on stored colon biopsies amplified a molecular product with 99 % sequence homology toC. belli . The patient improved promptly with trimethoprim-sulfamethoxazole treatment. Conclusion In the appropriate clinical context we suggest molecular testing forC. belli or an empirical therapeutic trial.